Research Evolution on Renewable Energies Resources from 2007 to 2017: A Comparative Study on Solar, Geothermal, Wind and Biomass Energy - Valencia Ochoa, Guillermo; Alvarez, Jose Nunez; Acevedo, Carlos (International Journal of Energy Economics and Policy, 2019)
This article presents a bibliometric analysis of trends and the research state on the main renewable energies based on information obtained from the SCIE / SSCI database for the period 2007-2017. The analysis is aimed at solar energy, geothermal energy, wind energy and biomass energy source. The results generated from the bibliometric techniques used allowed to obtain the behavior of the publications production and the influence that different countries and universities have on this subject. From the 10,363 publications, the 87.5% are journal articles and the 98% are in English language. In addition, 49.03% of the publications corresponded to solar energy, 33.83% to wind energy, 12.77% to biomass and 4.37% to geothermal energy. In the ten years analyzed, the United States has been the most influential country in this research area, presenting the largest volume of publications in each of the renewable energies source studied. The results of this paper provide to energy researchers a relevant overview of the tendencies and scope of the main renewable energies worldwide. In addition, to support scientific decision and prospective investment in research center, relevant data are presented on the countries producing these renewable energies and their relationship with the production of publications. Keywords: bibliometric research, renewable energies, solar energy, wind energy, geothermal energy, biomass energy. JEL Classifications: Q42 DOI: https://doi.org/10.32479/ijeep.8051